DRD4 genotyping may differentiate symptoms of attention-deficit/hyperactivity disorder and sluggish cognitive tempo - Bolat, Hilmi; Ercan, Eyup S.; Unsel-Bolat, Gul; Tahillioglu, Akin; Yazici, Kemal U.; Bacanli, Ali; Akin, Haluk (Assoc Brasileira Psiquiatria, 2020)
Objective: Studies to reduce the heterogeneity of attention-deficit/hyperactivity disorder (ADHD) have increased interest in the concept of sluggish cognitive tempo (SCT). The aim of this study was to investigate if the prevalence of two variable-number tandem repeats (VNTRs) located within the 3'-untranslated region of the DAT1 gene and in exon 3 of the dopamine D4 receptor (DRD4) gene differ among four groups (31 subjects with SCT but no ADHD, 146 individuals with ADHD but no SCT, 67 subjects with SCT + ADHD, and 92 healthy controls). Methods: We compared the sociodemographic profiles, neurocognitive domains, and prevalence of two VNTRs in SCT and ADHD subjects versus typically developing (TD) controls. Results: The SCT without ADHD group had a higher proportion of females and lower parental educational attainment. Subjects in this group performed worse on neuropsychological tests, except for psychomotor speed and commission errors, compared to controls. However, the ADHD without SCT group performed significantly worse on all neuropsychological domains than controls. We found that 4R homozygosity for the DRD4 gene was most prevalent in the ADHD without SCT group. The SCT without ADHD group had the highest 7R allele frequency, differing significantly from the ADHD without SCT group. Conclusion: The 7R allele of DRD4 gene was found to be significantly more prevalent in SCT cases than in ADHD cases. No substantial neuropsychological differences were found between SCT and ADHD subjects.
Keywords: attention-deficit/hyperactivity disorder; sluggish cognitive tempo; dopamine transporter gene; dopamine receptor D4 gene; psychomotor speed